In vitro antitumor activity of dialkylamine-1, 4-naphthoquinones toward human glioblastoma multiforme cells. (15th February 2022) - Clementino-Neto, José; da Silva, João Kaycke Sarmento; de Melo Bastos Cavalcante, Cibelle; da Silva-Júnior, Paulo Fernando; David, Cibelle Cabral; de Araújo, Morgana Vital; Mendes, Carmelita Bastos; de Queiroz, Aline Cavalcanti; da Silva, Elaine Cristina Oliveira; de Souza, Samuel Teixeira; da Silva Fonseca, Eduardo Jorge; da Silva, Tânia Maria Sarmento; et al.
Abstract : In this study, we evaluated the in vitro antitumor activity of dialkylamino-1, 4-naphthoquinones (1a–n ) toward human glioblastoma multiforme cells (GBM02). Abstract : In this study, we evaluated the in vitro antitumor activity of dialkylamino-1, 4-naphthoquinones (1a–n ) toward human glioblastoma multiforme cells (GBM02). All the derivatives inhibited GBM02 cell viability except for compounds 1a, 1b, and 1c . In contrast, compounds 1d, 1e, 1f, 1g, 1h, 1k, and 1n were the most effective ones. Among them, compound 1e was found to be the most promising analog (IC50 : 14.9 ± 4.6 μM). Compounds 1a, 1l, and 1n weren't toxic towards monocytes and lymphocytes, while compounds 1e, 1f, and 1g presented low cytotoxicity. Moreover, compounds 1e, 1f, 1g, 1k, and 1n were more selective for GBM02 cells than for monocytes and lymphocytes. Still, compounds 1e and 1n promoted changes in the morphology of tumor cells, induced apoptosis in GBM02 cells, and promoted cell cycle arrest in the S and G0 /G1 phases. Compounds 1e and 1n were more effective against GBM02 than temozolomide (TMZ). Furthermore, in silico studies suggest that these compounds have good oral bioavailability after intestinal absorption, have permeability to the blood–brain barrier, and are not inhibited by P-glycoprotein, remaining in the brain environment. In this sense, these two derivatives are effective antitumor agents and should be subjected to new experimental protocols in the antitumor drug development chain to become future therapeutic options for this disease of poor prognosis and, to date, no cure.